Selective growth of tin whiskers from its alloys on Ti2SnC. (1st October 2020) - Tang, Jingwen; Zhang, Peigen; Liu, Yushuang; Lu, Chengjie; Zhang, Yan; He, Wei; Tian, Wubian; Zhang, Wei; Sun, Zhengming
Abstract: The spontaneous growth of metal whiskers has been investigated for more than 70 years. However, there is still no agreement on its growth mechanism, and moreover, new characteristics of this whiskering phenomenon continue to emerge. In this study, Ti2 SnC is found to be capable of extracting Sn out of its alloys (SnBi, SnAg) by selectively growing Sn whiskers, and the Sn whiskers share the features of the traditional whiskers on platings and solders. Replacing the Ti2 SnC substrate with TiC or SiC, under the same conditions, however, the selective growth of Sn whisker does not happen, which means Ti2 SnC plays a critical role in it. Based on the unique crystal structure of Ti2 SnC, active Sn atoms diffusing through the basal planes of Ti2 SnC is proposed to explain the selectivity. The driving force is suggested to be the high interfacial energy between Ti2 SnC and tin. This study is of importance to further understand the growth mechanism of metallic whiskers, and it may be also possible to be harnessed to develop paradigm-shifting technologies of metal purification and metallic whisker/nanowire preparation.